Ukuran Kelompok Simpai (Presbytis Melalophos) Di Hutan Desa Cugung Kesatuan Pengelolaan Hutan Lindung Model Gunung Rajabasa Lampung Selatan - Cindy Yoeland Violita; Agus Setiawan; Elly Lestari Rustiati (Department of Forestry, Faculty of Agriculture, University of Lampung, 2015)
Cugung forest managed by Protection Forest Management Unit Model (KPHL) of Rajabasa Mountain, its a natural habitat for simpai (Presbytis melalophos). Its size and structure are not known. Research was done to observe its group size and population structure in Cugung forest using concentration count method. Group size was 11 individuals, with 4 reproductive age and 5 young individuals and 2 infants. Sexual ratio is 1:2. Keywords: simpai, group size, a cugung forest